Efeitos glicêmicos, cardiopulmonares e de composição corporal da auriculoterapia em pessoas com diabetes mellitus tipo 2: ensaio clínico controlado e randomizado - Brasileiro, Thaila Oliveira Zatiti (2018)
Diabetes Mellitus is a global health problem. It is a heterogeneous group of metabolic dysfunctions that has hyperglycemia in common. The objective of the study was to evaluate the effect of auriculotherapy on glycemic, cardiopulmonary and body composition parameters in the person with Diabetes Mellitus type 2 (DM2). It is a controlled, randomized and masked clinical trial performed between August and December 2017. The sample consisted of 44 people with DM2 who had been enrolled in the Vivver / e system for at least five years. -SUS of Primary Health Care in the city of Alfenas. After the initial evaluation, participants were allocated into two groups: the intervention group (n = 22), who received 05 auriculotherapy sessions and the control group (n = 22), who did not receive the intervention. All participants were evaluated by a trained professional, in three moments: before the intervention; one day after the last auriculotherapy session, and 15 days after the second evaluation (Follow up). For this, the instrument of characterization of the subject was used; monitoring of capillary glycemia; of body composition by body mass index, body mass index, body fat index, water index and muscle mass; and the cardiopulmonary condition by checking the maximum inspiratory and expiratory pressure, blood pressure, heart rate and respiratory rate. Data were analyzed by intention to treat. For the analysis the Shapiro Wilk Test was used to determine the normality of the data. The Mann Whitney and Wilcoxon Paired tests were used for the non-parametric data and the Student T-Test and Paired T-Test for the parametric. The mean value of capillary glycemia after the intervention in the intervention group was lower than in the control group. The mean values of weight and body mass index remained constant in preintervention, post-intervention and follow up. Regarding body fat index, there was statistical significance in the comparison between follow up and pre-intervention (p = 0.001). The present study showed that there was a positive clinical effect of auriculotherapy in the intervention group on capillary glycemia; in body fat index, and in blood pressure. Thus, it can be pointed out that the established treatment protocol can be considered as opportune in glycemic control and body composition.